THE ANALYSIS OF THE EFFECT OF THE ATM (AUTOMATED TELLER MACHINE) SERVICE DIMENSIONS ON CUSTOMERS SATISFACTION AT PT BANK PEMBANGUNAN DAERAH JAWA TENGAH BRANCH OFFICE OF KUDUS - Dhiah Fitriyani; Aris Sunindyo; Moh. Muslikh (FInance and Banking Program, Accounting Department, Politeknik Negeri Semarang, 2020)
This research aims to identify factors - factors the quality of service that consists of tangible, reliability, responsiveness, assurance, empathy to customer satisfaction PT. Bank Pembangunan Daerah Jawa Tengah Branch Office of Kudus. The population of this research is all of the customers at PT. Bank Pembangunan Daerah Jawa Tengah Branch Office of Kudus. The sampling technique uses the Accidental Sampling Method amounting to 100 customers. The data used in this research is the primary data obtained through the distribution of questionnaires. The data analysis model uses the Multiple Linear Regression Analysis Model. Meanwhile, data analysis techniques use the Statistical F Test, Coefficient of Determination (R2), and statistical t-Test.The results of t test are obtained the effect of variable responsiveness, assurance and empathy that significantly influence customer satisfaction of PT Bank Pembangunan Daerah Jawa Tengah Kudus Branch Office. Meanwhile reliability and tangible have no significant effect. In F test, it is found that the dimension of ATM Service quality tangible, reliability, responsiveness, assurance, and empathy simultaneously have significant effect on the satisfaction of customers of the Central Java Regional Development Bank of the Branch Office